Towards a Democratic Franchise : Suffrage Reform in the Twentieth-Century Bahamas - Aranha, Stephen B. (Global perspectives on legal history, 2022)
This book examines the process of electoral reform in the Bahamas during the 20th century in the broader context of decolonisation. Beginning with the General Assembly Elections Act of 1919, which reaffirmed a franchise limited to propertied men, milestones include the introduction of voting by secret ballot between 1939 and 1946, universal adult male suffrage in 1959, women's suffrage in 1961, and the incremental abolition of plural voting between 1959 and 1969.
Keywords: Suffrage : Bahamas : 20th century; Election law : Bahamas : 20th century